KEKUATAN KETERANGAN AHLI DALAM PEMBUKTIAN TINDAK PIDANA PEMBUNUHAN (Studi Kasus Putusan Nomor 777/Pid.B/2016/PN.JKT.PST Atas Nama Terdakwa Jessika Kumala Wongso) - Daniel Af Hutapea; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Justice is the responsibility of all law enforcement personnel, especially police, prosecutors and judges. Evidence is a problem that plays a role in the process of examining the trial. If the evidence proved by the law is "insufficient" to prove the guilt of the defendant, the defendant shall be released from punishment; on the other hand, if the defendant's error can be proven by the evidence referred to in article 184 KUHAP, the defendant shall be declared "guilty ". Based on the trial in the case of Jessika's murder of a victim called Mirna, the evidence in the trial only focuses on expert information only. In this case that actually used as evidence in the trial is based on the facts that occurred in the field is not but opinion and custom.This type of research can be classified in the type of normative legal research, the legal principle used as the problem object in the study is the principle contained in the criminal justice system, that a judge should be able to consider the facts of the trial to create a sense of justice. data sources used consisting of primary legal materials, secondary law materials, and tertiary legal materials, data collection techniques in this study by literature review method, after the data collected and then analyzed to be drawn conclusions.From the result of research and discussion it can be concluded that, First, the power of expert information in the proof of the crime of murder verdict Number 777 / Pid.B / 2016 / PN.JKT.PST on behalf of defendant Jessika Kumala Wongso is the evidence in the trial only focus on the expert's testimony, the judge judged the testimony of the expert witness to prove that Jessika Kumala Wongso was proven guilty, while on the other hand there was no evidence of the fact that the defendant had included cyanide (sodium cyanide) into the victim's drink or so-called Mirna. Secondly, the basis of the judge's legal considerations in deciding the criminal case Number 777 / Pid.B / 2016 / PN.JKT.PST on behalf of defendant Jessika Kumala Wongso is in the consideration of the judge asserted there should be no eyewitness who saw a person committing a criminal act. The judge may obtain from indirect evidenceKeywords: Justice - Proof - Judge Consideration